If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -4 = 3x + 4 Reorder the terms: -4 + 6x = 3x + 4 Reorder the terms: -4 + 6x = 4 + 3x Solving -4 + 6x = 4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -4 + 6x + -3x = 4 + 3x + -3x Combine like terms: 6x + -3x = 3x -4 + 3x = 4 + 3x + -3x Combine like terms: 3x + -3x = 0 -4 + 3x = 4 + 0 -4 + 3x = 4 Add '4' to each side of the equation. -4 + 4 + 3x = 4 + 4 Combine like terms: -4 + 4 = 0 0 + 3x = 4 + 4 3x = 4 + 4 Combine like terms: 4 + 4 = 8 3x = 8 Divide each side by '3'. x = 2.666666667 Simplifying x = 2.666666667
| 36=18x-12+6 | | 8x-6=4x+4 | | 7(6-38v)+27(11+13v)=-1 | | 10x+9=7x+6 | | y-x=-1 | | 5(x-3)+22=57 | | 2[3x+4(x-5)]-4x=12 | | 10-2q+5q= | | 2[3x+4(4x-5)]-4x=12 | | y=400x+200 | | 42n-23=6(12x-7) | | 173600=X+(X*1.12) | | 6x-6=9x+9 | | 4.93-9.2p=.66p | | 8y+11=-7y-19 | | 41-7x=2x+24 | | 5m-43=2m+80 | | 3x+6=x-8 | | 2x+8=4x+5 | | 6x^4-x^3=0 | | 7n-5=10n+13 | | y=x^4-6x^3+9x^2+4x-12 | | -6x=2y-10 | | 16+3x=8+32 | | 6y=5(y+11) | | 8-4x=6x-18 | | 2(4x-1)=7x-5(x+4) | | .33x+2=10 | | -6d+19=12 | | 0.35*(3048.24+x)=x | | -14p+6.3=-24.5 | | 11x-22=5x+2 |